Authentic project-based learning in grades 4-8 : standards-based strategies and scaffolding for success - Laur, Dayna (New York : Routledge,Taylor & Francis Group, 2020)
"Authentic Project-Based Learning in Grades 4-8 provides step-by-step instructions to help educators embed project-based learning (PBL) into your daily classroom routine. The author lays out five clear, standards-based stages you can use to process the what, how, and why of authentic project-based experiences and create PBL challenges in any subject area for your learners. You'll learn how to create projects that: - Align with your content standards - Integrate technology effectively - Support reading and writing development - Utilize formative assessment - Manage and engage with complex projects - Facilitate the development of essential skill beyond school Each chapter includes a variety of practical examples and tools you can use immediately. The tools are also provided on our website as free eResources for ease of implementation" --
Authentic concept creation -- Align content standards to the real world -- Support digital transformation -- Generate authentic reading and writing -- Formative assessments for success -- Levels of complexity -- Essential skills for tomorrow -- Commonly asked questions about PBL.
Includes bibliographical references.
Keywords: Project method in teaching; Education, Elementary -- Curricula; Middle school education -- Curricula; Academic achievement; Authentic learning